Pengaruh Lingkungan Kerja dan Perilaku Inovatif Terhadap Sustainable Perfomance Melalui Kepuasan Kerja - Riska Amelia Fatihah; Eko Nur Fu’ad (Penerbit Goodwood, 2025)
Purpose: Identifying and analyzing the influence of work environment and innovative behavior on sustainable performance through job satisfaction. Methodology: The population in this study were 334 employees of CV Kalingga Keling Jati. Data were collected from 210 respondents using random sampling techniques through online questionnaires distributed using Google Forms, then analyzed using the SEM-PLS method. Results: Work environment and innovative behavior have a significant impact on sustainable performance, with job satisfaction acting as a mediator that strengthens the impact. A supportive work environment and a culture of innovation have been shown to significantly improve operational efficiency and sustainability. Conclusion: The conclusion indicates that the work environment and innovative behavior significantly influence sustainable performance, both directly and through the mediation of job satisfaction. Job satisfaction strengthens this relationship, suggesting that organizational strategies fostering a supportive environment and encouraging innovation will enhance job satisfaction and lead to optimal sustainable performance. Limitations: This study is limited to data from CV Kalingga Keling Jati, so the results may be less general to other furniture industries. The quantitative method limits the exploration of qualitative aspects such as work culture and motivation, and does not analyze in depth external factors such as global market dynamics and government regulations. Contribution: This study provides insights into the role of work environment and innovative behavior in sustainable performance through job satisfaction, as well as a framework for research and practical application in related areas.